1991
DOI: 10.1254/jjp.57.463
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Interval-Related Effects of Class I Antiarrhythmic Drugs, Mexiletine, Cibenzoline and Disopyramide, on Ventricular Activation in Canine Myocardial Infarction.

Abstract: Time-dependent inhibition of sodium channels by class I antiarrhythmic drugs has been observed in isolated cardiac muscles or cells. We examined coupling interval-related effects of class I antiarrhythmic drugs, mexiletine, cibenzoline and diso pyramide, on ventricular activation in canine infarcted myocardium. A ventricular stimulation with various coupling intervals was applied to the right ventricle, and activation delays (time intervals between the initiation of a deflection and the final rapid deflection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…A similar effect was observed with class I antiarrhythmic drugs [16], which may be caused by a time-dependent inhibition of sodium channels [27]. However, it is not clear whether or not the mechanism of the coupling interval-related effects of the volatile anesthetics is similar to those of class I antiarrhythmic drugs.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A similar effect was observed with class I antiarrhythmic drugs [16], which may be caused by a time-dependent inhibition of sodium channels [27]. However, it is not clear whether or not the mechanism of the coupling interval-related effects of the volatile anesthetics is similar to those of class I antiarrhythmic drugs.…”
Section: Discussionmentioning
confidence: 61%
“…The present study showed that sevoflurane depressed the delayed activation in infarcted zones of canine ventricles. The effect of sevoflurane was selective to the A selective depression of the delayed activation was observed with class I antiarrhythmic drugs [16]. A previous study showed that halothane decreased the Vm in the isolated Purkinje fibers of infarcted hearts [8].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation